Implementation of Traditional Market Management Policy at Inpres Manonda Market, Palu City - Stefany Tandi Alla; Nuryana Haprin Dj Achmad (Penerbit Goodwood, 2026)
Purpose: This study aims to explain the implementation of traditional market management policy at Inpres Manonda Market, Palu City. Methodology/Approach: A descriptive qualitative approach was applied, with research conducted at the Department of Trade and Industry of Palu City. Data were collected through observation, interviews, and documentation, and analyzed through data reduction, data display, and conclusion drawing. Results/Findings: The study found that policy implementation still faces challenges, especially in market order and cleanliness. Despite coordination with Satpol PP, the Armed Forces, and the Transportation Agency, many vendors continue selling on the roadside, causing congestion. Cleanliness remains suboptimal due to garbage accumulation and lack of trash bins. Supporting factors include officer commitment and agency collaboration, while barriers are limited skilled personnel and inadequate infrastructure. Conclusion: The implementation of the Inpres Manonda Market management policy has not been fully effective. Strong institutional support exists, but weaknesses in infrastructure and human resources hinder optimal results. Addressing these gaps is crucial for better governance and sustainable local economic development. Limitations: The study is limited to one market, so findings are not representative of all traditional markets in Palu City. The qualitative method also relies heavily on perceptions and observations. Contribution: This study provides empirical evidence on barriers and supporting factors in policy implementation, offering practical input for local governments and theoretical insight into the interaction of institutional support and infrastructure readiness.